"Girls don't have big tummies": The experiences of weight-related discussions for children with autism spectrum disorders. (July 2019) - Jachyra, Patrick; Anagnostou, Evdokia; Knibbe, Tara Joy; Petta, Catharine; Cosgrove, Susan; Chen, Lorry; Capano, Lucia; Moltisanti, Lorena; McPherson, Amy C
Children with autism spectrum disorders appear to be at a higher risk of having obesity than their typically developing peers. Although it has been recommended that healthcare providers speak to children with autism spectrum disorders about the potential health risks of unhealthy weight, no previous research has explored how healthcare providers communicate with them about this topic. The purpose of this study was to explore children's perspectives and experiences of discussing weight-related topics in healthcare consultations. Eight children were interviewed, and an interpretive phenomenological analysis informed the research approach and analysis of the data. Results indicated that weight-related discussions with healthcare providers were often met with trepidation, anxiety, anger, and frustration. Children also expressed that they experienced weight stigma in clinical visits and everyday interactions. Weight stigma was often (unwittingly) projected by healthcare providers during appointments and had debilitating effects on children. Finally, higher weights emerged as a repetitive/restricted interest, and children reported body image challenges regarding their higher weights. Frameworks and tools that are specific to the needs and abilities of children with autism spectrum disorders are needed for healthcare providers to foster positive conversations about weight-related topics in an effort to promote lifelong wellness.